2015
DOI: 10.1073/pnas.1508170112
|View full text |Cite
|
Sign up to set email alerts
|

Resource colimitation governs plant community responses to altered precipitation

Abstract: Ecological theory and evidence suggest that plant community biomass and composition may often be jointly controlled by climatic water availability and soil nutrient supply. To the extent that such colimitation operates, alterations in water availability caused by climatic change may have relatively little effect on plant communities on nutrient-poor soils. We tested this prediction with a 5-y rainfall and nutrient manipulation in a semiarid annual grassland system with highly heterogeneous soil nutrient suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
119
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 63 publications
20
119
2
Order By: Relevance
“…The PCA and the change in the relative AGB of the PFGs also indicated that the shift patterns were mainly derived from precipitation changes. The findings agree with some other studies reported that altered precipitation notably shifted plant community composition in semiarid grasslands (Eskelinen & Harrison, ; Yang et al, ). However, the sensitivity of plant community composition to precipitation changes could be mediated by other limited resource such as N, largely depending on environmental conditions such as soil nutrient pools (Eskelinen & Harrison, ).…”
Section: Discussionsupporting
confidence: 93%
“…The PCA and the change in the relative AGB of the PFGs also indicated that the shift patterns were mainly derived from precipitation changes. The findings agree with some other studies reported that altered precipitation notably shifted plant community composition in semiarid grasslands (Eskelinen & Harrison, ; Yang et al, ). However, the sensitivity of plant community composition to precipitation changes could be mediated by other limited resource such as N, largely depending on environmental conditions such as soil nutrient pools (Eskelinen & Harrison, ).…”
Section: Discussionsupporting
confidence: 93%
“…Fen and bog vegetation respond contrastingly to WLD; while fen communities were pushed from their initial states to vegetation succession, ombrotrophic communities showed higher inter‐annual variation but stayed within their initial state over the sixteen years following drainage. This pattern found here for peatland vegetation agrees with the general theory first grounded in grasslands and forests (Davis, Grime, & Thompson, ; Eskelinen & Harrison, ; Roberts & Gilliam, ) that mesic communities are more sensitive than nutrient‐poor communities to environmental perturbation.…”
Section: Discussionsupporting
confidence: 90%
“…Predicting ecosystem responses to global change is a fundamental issue in ecology. It has been well documented that the aboveground plant community is sensitive to precipitation change (Cleland et al, 2013;Eskelinen and Harrison, 2015) and N deposition (Stevens et al, 2004;Clark and Tilman, 2008), particularly in arid and semi-arid grassland ecosystems, where water and N are generally considered to be limiting resources (Harpole et al, 2007;Yang et al, 2011;Xu et al, 2012b). A growing body of evidence suggests that higher precipitation increases plant species richness (Bai et al, 2008;Xu et al, 2015b), whereas N fertilization is reported as the main driver of the loss of species richness (Gough et al, 2000;Stevens et al, 2004;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%